2004
DOI: 10.1529/biophysj.104.042226
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Frequency Windows and the Protein Dynamical Transition

Abstract: Proteins undergo an apparent dynamical transition on temperature variation that has been correlated with the onset of function. The transition in the mean-square displacement, AEDr 2 ae, that is observed using a spectrometer or computer simulation, depends on the relationship between the timescales of the relaxation processes activated and the timescale accessible to the instrument or simulation. Models are described of two extreme situations-an ''equilibrium'' model, in which the long-time dynamics changes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
96
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 38 publications
7
96
0
Order By: Relevance
“…For example, it has been reported that the transition is coupled to the onset of translational motions in hydration water [47][48][49]. In addition, it has been debated whether the transition is a real phenomenon, or merely a manifestation of the fact that the measurable atomic dynamics enter the experimentally accessible resolution window above certain temperatures [17,18,24,25,27]. In such a scenario, the dynamic motions of the biomolecules may increase without any discontinuity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been reported that the transition is coupled to the onset of translational motions in hydration water [47][48][49]. In addition, it has been debated whether the transition is a real phenomenon, or merely a manifestation of the fact that the measurable atomic dynamics enter the experimentally accessible resolution window above certain temperatures [17,18,24,25,27]. In such a scenario, the dynamic motions of the biomolecules may increase without any discontinuity.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamical properties of these water molecules, closely resembling that of a glassy system [1,2], and, in particular, the interplay with the slaved dynamical behavior of the protein itself, has likely implications for biological functionality [3][4][5][6], and as such is a subject of active research. The accurate study of the properties of water molecules hydrating proteins has seen a resurgence of interest in the past few years, possibly due to the availability of powerful simulation techniques along with the advent of new experimental approaches.…”
mentioning
confidence: 99%
“…[33,38] The concept has also been incorporated into the formalism that describes the dynamics accompanying the glass transition in molecular systems. When the protein relaxation time decreases with temperature, as it usually does, it has been shown that measurement of r 2 R over a finite time window can introduce an apparent DT when there is no actual change in the elastic incoherent DSF, S(Q, ω = 0).…”
Section: Introductionmentioning
confidence: 99%
“…When the protein relaxation time decreases with temperature, as it usually does, it has been shown that measurement of r 2 R over a finite time window can introduce an apparent DT when there is no actual change in the elastic incoherent DSF, S(Q, ω = 0). [33,38] To avoid this issue, identification and use of an intrinsic, long time MSD r 2 would be helpful. Several MD studies have been performed aimed at understanding the origin of elastic neutron scattering from proteins.…”
Section: Introductionmentioning
confidence: 99%